Health saving as strategic direction of teaching staff training - Lydia Valentinivna, Kondrashova (2020)
The article examines the health of future teachers through the educational process. The relationship between trends in the development of pedagogical education with the unpreparedness of future teachers and teachers-practitioners to We came to the conclusion that health education - is the organization of training, which provides accounting for the capabilities and abilities of the individual, creates appropriate conditions for protection, preservation and individual abilities, maximum disclosure of physical, mental, spiritual and moral potential, achieving important personal goals for a healthy lifestyle. It has been confirmed that the practice of health education is formal, because high school teachers are not prepared for this type of activity. An indicator of the effectiveness of training future teachers for professional activities is their readiness for healthy education of young people. It is established that readiness for health education involves the ability to use knowledge of the theoretical foundations of health, mastering the methods of health, value orientations, the need for creative self-expression, evaluative-reflexive correction and prevention of factors that negatively affect the well-being of participants. This complex personal education in its development goes from low, medium to high levels, which differ in the degree of manifestation of criteria and indicators. It is emphasized that the health of young people is an important strategy for optimizing modern education and a prerequisite for its quality.